PENGARUH MODEL AUDITORY INTELLECTUALLY REPETITION TERHADAP KEMAMPUAN PEMECAHAN MASALAH DALAM PEMBELAJARAN BIOLOGI MELALUI LESSON STUDY FOR LEARNING COMMUNITY - Ulvi Atika Suri; Eko Retno Mulyaningrum (Bioma : Jurnal Ilmiah Biologi, 2019)
ABTRACTThe development of the 21st century skills requires educators to prepare students for global economic competition by having special skills, one of which is problem solving. Achievement of the 21st skills century is done by improving the teaching profession, one of which is through lesson study for learning community. The purpose of this study is to determine whether there is an influence on the application of the auditory intellectually repetition (AIR) learning model through lesson study for learning community on the problem solving abilities of students. This study uses a quasi experimental design method through the randomized posttest-only control group design using matched subjects. The study was conducted at Semarang 11 Public High School in the 2018/2019 school year. Based on the research, the results of statistical tests on the problem solving ability variable have a significance value (2-tailed) of 0.000 <0.05 so that it can be concluded that there are significant differences in students' problem solving abilities between the experimental class and the control class. The experimental class scored better than the control class, with the acquisition of the experimental class number of 76.96 and the control class of 65.94. Based on these results it can be concluded that the application of auditory intellectually repetition (AIR) learning models through lesson study for learning community can improve students' problem solving abilitiesKeywords: Auditory Intellectually Repetition (AIR) Learning Model, Lesson Study for Learning Community, Problem Solving